Chapter The Student Voice in Higher Education and the Implications of Promoting Faculty Development - Fedeli, Monica (Studies on Adult Learning and Education, 2018)
This chapter presents a literature overview of the student voice in higher education, the main results from a three-year research project conducted at five Italian universities with the aim of investigating students' voices in higher education and how they offer insight into fostering Faculty Development